Health conditions and lifestyle risk factors of adults living in Puerto Rico: a cross-sectional study - Josiemer Mattei; Martha Tamez; Carlos F. Ríos-Bedoya; Rui S. Xiao; Katherine L. Tucker; José F. Rodríguez-Orengo (BMC, 2018)
Abstract Background Puerto Rico is experiencing an economic and healthcare crisis, yet there are scarce recent and comprehensive reports on the population's health profile. We aimed to describe prevalent risk factors and health conditions of adults living in Puerto Rico and assess their interrelationship. Methods Participants (n = 380) aged 30-75y recruited from a 2015 convenience sample in primary care clinics in the San Juan, Puerto Rico metropolitan area answered cross-sectional interviewer-administered questionnaires on sociodemographic characteristics, lifestyle behaviors, self-reported medically-diagnosed diseases, health services, and psychosocial factors. Anthropometric measures were obtained. Logistic regression models assessed factors associated with having ≥2 cardiometabolic conditions or ≥ 2 chronic diseases. Results Most participants had completed ≥college education (57%), had household income <$10,000/y (60%), received government-assisted food benefits (51%), and had health insurance (93%). Nearly 20% reported smoking, 27% alcohol use, 74% light/sedentary physical activity, 51% sleeping difficulties, and 36% self-rated fair/poor diet. Social support was moderate, and 53% screened positive for depressive symptomatology. Abdominal obesity was observed in 33% of men and 76% of women (p < 0.0001). Self-reported medically-diagnosed conditions included hypertension (39%), anxiety (30%), obesity (28%), arthritis (26%), hypercholesterolemia (24%), depression (22%), respiratory problems (21%), and diabetes (21%). Higher odds of having ≥2 cardiometabolic conditions (37%) was observed among participants aged ≥50y, with sedentary physical activity, and self-rated fair/poor diet. Odds of having ≥2 chronic diseases (62%) were higher among ≥50y, sleeping difficulties, > 2 h/day television, and self-rated fair/poor diet. Participants obtained (79%) and trusted (92%) health information from physicians. While most participants with a cardiometabolic condition reported receiving medical recommendations on diet (> 73%) and physical activity (> 67%), fewer followed them (< 67% and < 53%, respectively), yet most adhered to medication treatments (> 73%). Participants following medical recommendations were more likely to report healthy vs. poor behaviors (90% vs. 75%, self-rated diet); (73% vs. 56%, physical activity). Conclusions Adults living in Puerto Rico have multiple lifestyles risk factors and high prevalence of chronic diseases, namely cardiometabolic and psychological conditions. Comprehensive epidemiological studies are needed to identify contributors to chronic disease, including lifestyle behaviors. Concerted multi-level public health and clinical programs should be prioritized to help this population improve their health.